2012
DOI: 10.1113/jphysiol.2011.215137
|View full text |Cite
|
Sign up to set email alerts
|

Patterned control of human locomotion

Abstract: There is much experimental evidence for the existence of biomechanical constraints which simplify the problem of control of multi-segment movements. In addition, it has been hypothesized that movements are controlled using a small set of basic temporal components or activation patterns, shared by several different muscles and reflecting global kinematic and kinetic goals. Here we review recent studies on human locomotion showing that muscle activity is accounted for by a combination of few basic patterns, each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
264
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(284 citation statements)
references
References 68 publications
(119 reference statements)
15
264
3
2
Order By: Relevance
“…In a healthy population, the rectus femoris is activated for weight acceptance directly at initial contact and in the early stance phase. 40 In our study, the CAI group activated the rectus femoris an average of 108 milliseconds earlier than the control group. This earlier preactivation of the rectus femoris may be due to the decreased pronation in participants with CAI.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In a healthy population, the rectus femoris is activated for weight acceptance directly at initial contact and in the early stance phase. 40 In our study, the CAI group activated the rectus femoris an average of 108 milliseconds earlier than the control group. This earlier preactivation of the rectus femoris may be due to the decreased pronation in participants with CAI.…”
Section: Discussionmentioning
confidence: 88%
“…Our findings indicated that healthy individuals did not activate the peroneus longus until approximately midstance in the gait cycle, which is supported in gait-analysis studies. 40 In addition, the biomechanical function of the peroneus longus should be considered for its contribution to lateral dynamic stability of the ankle in weight bearing because of its role in propulsion during gait but not for its ability to actively evert the ankle. As the peroneus longus exerts a plantar-flexion force at the ankle and pulls down the first ray, assisting in pronation and subsequently stabilizing the first ray as a rigid lever for propulsion, the increased muscle tone provides tremendous dynamic stability to the lateral ankle.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with ACL deficiency alter their muscle activations when doing a certain task due to the lack of ACL. It is believed that muscles are activated synergistically following a certain pattern depending on the motor task (Lacquaniti et al, 2012;Ting and McKay, 2007;Ting, 2007;Ting et al, 2012), that is to say, our Central Nervous System (CNS) does not activate the muscles independently. Muscle synergies are represented by modules consisting of one Neural Command (NC), which represents the time activation of a set of muscles, and one Synergy Vector (SV), which represents the weighting factor of each muscle to its NC (Ting and Macpherson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These originate from locomotor modules, which are in turn part of the neuronal networks of the spinal cord (Cappellini et al, 2006;Dominici et al, 2011;Ivanenko et al, 2004bIvanenko et al, , 2005Ivanenko et al, , 2006Lacquaniti et al, 2012a,b;Neptune et al, 2009). In humans, two of these basic patterns (essential for support during stance and to drive the limb during swing) are already present in neonates (Dominici et al, 2011;Lacquaniti et al, 2012b). Neonatal rats possess the same two basic patterns (Dominici et al, 2011;Lacquaniti et al, 2012b), and it is suggested that this most probably holds true for other animals as well (Dominici et al, 2011;Grillner, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Latash, 2008;Nishikawa et al, 2007). The latter is initiated at the cortical level and signals descend (via lower brain centres) the spinal cord to activate coupled spinal neural networks (central pattern generators, CPGs), which transform the command into coordinated muscle-tendon actions distributed over the limbs and joints (Grillner, 2011;Grillner et al, 2000;Lacquaniti et al, 2012b;Latash, 2008;Orlovsky et al, 1999).…”
Section: Introductionmentioning
confidence: 99%